Ventriculosagittal sinus shunt for treating hydrocephalus with elevated cerebrospinal fluid protein - Yikang Wang; Di Wang; Yu Tian; Yilong Yao; Qi Yu (Fluids and Barriers of the CNS)
Abstract  This study aimed to investigate the feasibility, acceptability, and preliminary efficacy of a ventriculosagittal sinus (VSS) shunt in the treatment of hydrocephalus with elevated cerebrospinal fluid (CSF) protein content. In this single-center retrospective analysis, we enrolled 80 patients with hydrocephalus and elevated CSF protein levels. Based on these procedures, primary cohort was divided into two groups using CSF protein (CSFP) for subsequent analysis to determine the relationship between the clinical effect and CSFP. Preoperative and postoperative computer tomography (CT) scans, clinical symptoms, and CSF laboratory test were compared. Clinical records of 80 patients were analyzed; 44 patients received VSS shunt, 30 patients received ventriculoperitoneal (VP) shunt, and 6 patients received ventriculobladder (VB) shunt. The most significant changes in ventricular size in the VSS shunt group were detected on the 7th day postoperatively from the collected imaging data. Six months after shunt surgery, the overall success rate for VSS shunt (35 of 44, 79.5%) was markedly higher than that for VP shunt (12 of 30, 40%) and VB shunt (1 of 6, 16.7%). The VSS shunt has a positive clinical effect in hydrocephalus with abnormal CSF laboratory results (elevated protein levels), which is more significant than the clinical success rate of VP shunt in terms of both symptoms and imaging results. The degree of relief and improvement of imaging and symptoms were unrelated to the CSFP content. There was no significant difference in the efficacy of VSS shunt between the CSFP < 1.0 g/L group and the CSFP > 1.0 g/L group. No intracranial or extracranial complications related to the surgery were noted during follow-up. The VSS shunt should be considered the first-line treatment option in cases of hydrocephalus with elevated CSFP levels. Moreover, VSS shunt can immediately improve symptoms and alleviate hydrocephalus even though the CSFP was elevated.